2023
DOI: 10.3389/fonc.2022.1087989
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic lethal interactions of DEAD/H-box helicases as targets for cancer therapy

Abstract: DEAD/H-box helicases are implicated in virtually every aspect of RNA metabolism, including transcription, pre-mRNA splicing, ribosomes biogenesis, nuclear export, translation initiation, RNA degradation, and mRNA editing. Most of these helicases are upregulated in various cancers and mutations in some of them are associated with several malignancies. Lately, synthetic lethality (SL) and synthetic dosage lethality (SDL) approaches, where genetic interactions of cancer-related genes are exploited as therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 194 publications
0
2
0
Order By: Relevance
“…Using patients’ data in The Cancer Genome Atlas, we have previously examined the expression of DDX41 in 24 different cancer types and found that DDX41 is up-regulated in most cancers [ 85 ]. In addition, we found that the predominant mutant DDX41 R525H protein has reduced ATP hydrolysis and DNA unwinding activities but retains normal strand annealing activity that causes excessive innate immune activation [ 69 ].…”
Section: Drug Development Targeting Ddx41mentioning
confidence: 99%
“…Using patients’ data in The Cancer Genome Atlas, we have previously examined the expression of DDX41 in 24 different cancer types and found that DDX41 is up-regulated in most cancers [ 85 ]. In addition, we found that the predominant mutant DDX41 R525H protein has reduced ATP hydrolysis and DNA unwinding activities but retains normal strand annealing activity that causes excessive innate immune activation [ 69 ].…”
Section: Drug Development Targeting Ddx41mentioning
confidence: 99%
“…Importantly, eIF4A3 was the only helicase found in our analysis and showed the highest degree of essentiality among members of the DEAD box family of enzymes (Supplementary Fig. S1A ), implicated in the treatment of both solid tumors and blood cancers [ 8 ].
Fig.
…”
Section: To the Editormentioning
confidence: 99%